Methyltransferase-like 7B participates in bladder cancer via ACSL3 m6A modification in a ferroptosis manner - Jiani He; Changming Dong; Xiandong Song; Zhongkai Qiu; Hao Zhang; Yuanjun Jiang; Tao Liu; Xiaojun Man (Biology Direct)
Abstract Background Bladder cancer (BC) is a malignant tumor. Methyltransferase-like 7B (MEETL7B) is a methyltransferase and its role in BC has not yet been revealed. Method Stable METTL7B knockdown or overexpression were achieved by lentiviral transduction in SW780 and TCCSUP cell lines. Xenografts tumors were established via subcutaneous injection of stable transfectants in BALB/c mice. Results A database search indicated that METTL7B was elevated in BC and it was validated in BC cell lines. METTL7B silencing suppressed cell proliferation and tumorigenesis in vitro and in vivo. Besides, METTL7B knockdown induced cell cycle arrest in G1 phase with a reduction in cyclin D1(CCND1), CDK4, and CDK6 levels and an elevation in CDKN2D levels in cells. Considering that ferroptosis is emerging as a therapeutic target for cancer, and the possible relationship between METTL7B and antioxidant enzymes. We, here, examined that ectopic METTL7B expression abolished ferroptosis markers in cells raised by Erastin treatment, including the production of lipid ROS, the increased cellular iron and MDA content, the decreased gene expression of ACSL3, FANCD2, and FADS2, as well as the mitochondrial injury observed by electron microscopy. Mechanically, ectopic METTL7B expression promoted m6A modification on ACSL3 mRNA. Gain of functional experiment exhibited that METTL7B inhibited Erastin-induced ferroptosis via ACSL3. Overexpressed PLAGL2 is identified as a possible independent predictor in BC and bioinformatics predicted the potential binding sites between PLAGL2 and METTL7B promoter region. Dual luciferase and chromatin immunoprecipitation analysis provided evidence that PLAGL2 directly binds to METTL7B promoter region. Conclusions METTL7B is involved in BC development and progression. METTL7B may mediate m6A modification on ACSL3 mRNA to negatively regulate ferroptosis in BC cells, which provides a potential therapeutic target for BC via ferroptosis. Graphical Abstract